Europeanization in Regional Museums? - Łucja Piekarska-Duraj (Ksiegarnia Akademicka Publishing, 2018)
European museums have undergone major changes in recent decades, mirroring many of the social and cultural processes taking place in Europe. Two of the main issues that have shaped the public discourse concerning cultural heritage are that of democratization and civil participation, both of which have not only mobilized policies but also redefined musealized heritage. At the same time, a ‘new museology’ approach, where heritage is understood as a dynamic construct, shared and interpreted by communities rather than monopolized by external authorities, has inspired many museums to rethink their visions and programs. While heritage democratization processes may be found both in the Lund and Tarnów museums, there are considerable differences between the two of them. The article examines these with the use of several concepts from core civilizational ideas such as: utility, progress, dignity, democratic governance and inclusion. In both cases, heritage is used to support the present political legacy: in the Swedish case, the emphasis is openly put on diversity and civil empowerment, whereas in Tarnów the narrative of past glory overwhelms other aspects of the past. Nevertheless, it is the European concept of the ‘person’ which stands behind both of them, however vague and complex its conceptualization may be.